Church and State as Seen in the Formation of Christendom - Allies, T. W. (Thomas William), 1813-1903 (Salt Lake City, UT : Project Gutenberg, 2012)
"Church and State as Seen in the Formation of Christendom" by T. W. Allies is a historical account written in the late 19th century. The text delves into the intricate relationship between the civil and spiritual powers from the biblical creation through key historical moments leading up to the establishment of Christendom. This exploration reveals insights into how these two domains have shaped societal structures and governance in conjunction with religious authority. The opening of the work introduces the foundational concepts of man's creation and the roles of Adam and Noah in both civil governance and religious worship. Allies emphasizes the divine origins of these roles and the implications of Adam's sin, which brought about the need for redemption through Christ. The author outlines the promise of salvation that hangs over humanity and discusses the initial unity of the human family, noting how sin led to the fragmentation of society. Themes of original sin, the establishment of marriage, and the institution of sacrifice are woven into the narrative to illustrate the theological basis on which societal order is built, setting the stage for the detailed examination of church and state dynamics throughout history. (This is an automatically generated summary.)
Release date is 2012-01-09
E-text prepared by Steven Giacomelli, Jeannie Howse, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/Canadian Libraries (http://www.archive.org/details/toronto)
Keywords: Church history -- Primitive and early church, ca. 30-600; Church and state; Religion and state